METTL1 promotes neuroblastoma development through m7G tRNA modification and selective oncogenic gene translation - Ying Huang; Jieyi Ma; Cuiyun Yang; Paijia Wei; Minghui Yang; Hui Han; Hua Dong Chen; Tianfang Yue; Shu Xiao; Xuanyu Chen; Zuoqing Li; Yanlai Tang; et al. (BMC, 2022)
Abstract Background Neuroblastoma (NBL) is the most common extra-cranial solid tumour in childhood, with prognosis ranging from spontaneous remission to high risk for rapid and fatal progression. Despite existing therapy approaches, the 5-year event-free survival (EFS) for patients with advanced NBL remains below 30%, emphasizing urgent necessary for novel therapeutic strategies. Studies have shown that epigenetic disorders play an essential role in the pathogenesis of NBL. However, the function and mechanism of N7-methylguanosine (m7G) methyltransferase in NBL remains unknown. Methods The expression levels of m7G tRNA methyltransferase Methyltransferase-like 1 (METTL1) were analyzed by querying the Gene Expression Omnibus (GEO) database and further confirmed by immunohistochemistry (IHC) assay. Kaplan-Meier, univariate and multivariate cox hazard analysis were performed to reveal the prognostic role of METTL1. Cell function assays were performed to evaluate how METTL1 works in proliferation, apoptosis and migration in cell lines and xenograft mouse models. The role of METTL1 on mRNA translation activity of NBL cells was measured using puromycin intake assay and polysome profiling assay. The m7G modified tRNAs were identified by tRNA reduction and cleavage sequencing (TRAC-seq). Ribosome nascent-chain complex-bound mRNA sequencing (RNC-seq) was utilized to identify the variation of gene translation efficiency (TE). Analyzed the codon frequency decoded by m7G tRNA to clarify the translation regulation and mechanism of m7G modification in NBL. Results This study found that METTL1 were significantly up-regulated in advanced NBL, which acted as an independent risk factor and predicted poor prognosis. Further in NBL cell lines and BALB/c-nu female mice, we found METTL1 played a crucial role in promoting NBL progression. Furthermore, m7G profiling and translation analysis revealed downregulation of METTL1 would inhibit puromycin intake efficiency of NBL cells, indicating that METTL1 did count crucially in regulation of NBL cell translation. With all tRNAs with m7G modification identified in NBL cells, knockdown of METTL1 would significantly reduce the levels of both m7G modification and m7G tRNAs expressions. Result of RNC-seq shew there were 339 overlapped genes with impaired translation in NBL cells upon METTL1 knockdown. Further analysis revealed these genes contained higher frequency of codons decoded by m7G-modified tRNAs and were enriched in oncogenic pathways. Conclusion This study revealed the critical role and mechanism of METTL1-mediated tRNA m7G modification in regulating NBL progression, providing new insights for developing therapeutic approaches for NBL patients.